2011
DOI: 10.1002/anie.201005921
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing the Use of Platinum in Hydrogen‐Evolving Electrodes

Abstract: One layer is enough: A new catalyst comprising a platinum monolayer on tungsten monocarbide (WC) could lead to inexpensive and efficient (photo)electrochemical production of molecular hydrogen (see scheme). The system uses far less platinum than conventional platinum‐foil electrodes but is just as effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
100
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(100 citation statements)
references
References 31 publications
0
100
0
Order By: Relevance
“…Chen and coworkers recently reported that such a catalyst exists for the hydrogen evolution reaction. [186][187][188] They found that a monolayer of Pt on WC exhibited the same hydrogen evolution activity as bulk Pt. Even so, the same catalyst exhibited poor activity for the ORR, most likely because the WC formed a WO x phase at high potentials.…”
Section: Strategies To Improve the Performance Of Pt-alloy Nanoparticlesmentioning
confidence: 99%
“…Chen and coworkers recently reported that such a catalyst exists for the hydrogen evolution reaction. [186][187][188] They found that a monolayer of Pt on WC exhibited the same hydrogen evolution activity as bulk Pt. Even so, the same catalyst exhibited poor activity for the ORR, most likely because the WC formed a WO x phase at high potentials.…”
Section: Strategies To Improve the Performance Of Pt-alloy Nanoparticlesmentioning
confidence: 99%
“…Many scientists also made large efforts to search other novel materials for HER catalysis [10][11][12]. On one hand, it was reported that the noble metals are the most active materials for HER catalysis [13,14]. However, pure noble metals are too expensive for the industry.…”
Section: Introductionmentioning
confidence: 99%
“…In these studies, advanced catalysts for the hydrogen evolution reaction (HER) are generally needed to reduce the overpotential and increase the catalytic current density. To date, the most effective electrocatalysts for HER are based on Pt-group metals, which are capable of catalyzing HER at a significant rate with almost no overpotential [5][6][7]. However, their scarcity and high costs of Pt-group metals have hindered their wide applications.…”
Section: Introductionmentioning
confidence: 99%
“…However, the catalytic activity of the above reported catalysts can't be compared with that of Pt-based electrocatalysts. It remains a great challenge to minimize the use of platinum to obtain the same high active HER catalysts [5,15,16].…”
Section: Introductionmentioning
confidence: 99%